Genomic adaptation of Clostridium perfringens to human intestine - Ke Wu; Juan Wang; Zelin Yan; Yanyan Zhu; Shaolin Wang; Bo Fu; Chengtao Sun; Ruichao Li; Edward M. Fox; Séamus Fanning; Li Bai; Yang Wang; et al. (iMetaOmics)
Abstract Clostridium perfringens is often associated with foodborne diseases, posing significant public health risks. However, genomic investigation of C. perfringens isolates from the human population has been lacking. This study aims to fill this knowledge gap by examining the genomic characteristics of C. perfringens isolates from 699 individuals at a provincial hospital in China. We further conducted evolutionary and pan‐genomic analyses, incorporating isolates from humans and animals worldwide. The results reveal potential regional and transregional transmission of C. perfringens among individuals, along with the common transfer of small gene clusters during this process. Notably, the food poisoning‐associated toxin gene cpe was identified in a fusion plasmid for the first time in an isolate, indicating fusion of pCP13‐like and pCW3‐like plasmids and the potential for transfer of cpe across genetic backgrounds. Moreover, we observed that the genomic characteristics of C. perfringens correlate with host species, with specific toxin genes, such as pfoA and colA, potentially influencing host selectivity. Through this comprehensive genomic analysis, we provide novel insights into the fusion of pCW3‐like and pCP13‐like plasmids, the genetic location of cpe, the transmission dynamics of C. perfringens strains, and the relationship between toxin genes and host relevance. These findings expand our understanding of C. perfringens and its implications for public health.